Analisis Self Confidence pada Pembelajaran Matematika Siswa Madrasah Aliyah - Ismiasih, Novi; Mustika, Tito Nur (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2024)
Students are often afraid of failing and making mistakes, this fear triggers students' low self-confidence. Confidence or self confidence is an important aspect of a person's personality. Self confidence is a part that students must have in order to be able to carry out mathematics learning well. Students who have self confidence in studying mathematics will get maximum results, because self confidence plays an important role in student academic achievement. This research uses qualitative with descriptive type. The research subjects were 23 class XII students majoring in languages. The instrument in this research was a non-test instrument, namely a mathematical self confidence questionnaire consisting of 12 statements. The results showed that (1) 79.02% believed in their own abilities, (2) 52.9% acted independently in making decisions (3) 65.8% had a positive self-concept, (4) 82.76% were brave express an opinion. Meanwhile, the average percentage of all indicators is 70.12% who have good self-confidence and 29.88% lack self-confidence in learning mathematics.